Status Kualitas Air di Kolam Bekas Tambang Batubara di Tambang Satui, Kabupaten Tanah Laut, Kalimantan Selatan - Said, Nusa Idaman; Yudo, Satmoko (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2021)
ABSTRACT Coal mining can have positive and negative impacts on the environment. The positive effects include providing new employment opportunities and increasing regional income as well as foreign exchange. In comparison, negative consequences could be the changes in the environment's quality and sustainability, caused by the formation of ex-mining pits and acid mine drainage, which reduce the quality of surrounding soil and water. This study aimed to determine the water quality of the ex-mining ponds at the Antasena Pit, Satui Mine, Kintap District, Tanah Laut Regency, South Kalimantan. This research measured the ponds' water quality directly on site. Meanwhile, the water samples were taken and analyzed in the laboratory. The laboratory analyzes showed that, in general, the physicochemical and biological parameters were under Class 1 Water Quality Standards of the Government Regulation Number 82 the Year 2001 on Water Quality Management and Water Pollution Control. Keywords : coal mining, ex-mining ponds, pond water quality Â ABSTRAK Penambangan batubara dapat memberikan dampak positif dan negatif terhadap lingkungan. Dampak positif tersebut antara lain membuka lapangan kerja baru dan meningkatkan pendapatan daerah serta devisa negara. Sedangkan dampak negatifnya adalah terjadinya perubahan kualitas dan kelestarian lingkungan akibat terbentuknya lubang bekas tambang dan timbulnya air asam tambang yang menurunkan kualitas tanah dan air di sekitarnya. Tujuan penelitian ini adalah untuk mengetahui kualitas air kolam bekas penambangan di Pit Antasena, Tambang Satui, Kecamatan Kintap, Kabupaten Tanah Laut, Kalimantan Selatan. Kualitas air kolam diukur langsung di lokasi dan sampel air diambil dan dianalisis di laboratorium. Analisis laboratorium menunjukkan bahwa secara umum parameter fisika-kimiawi dan biologi telah sesuai dengan Standar Kualitas Air Kelas 1 sesuai Peraturan Pemerintah RI Nomor 82 Tahun 2001 tentang Pengelolaan Kualitas Air dan Pengendalian Pencemaran Air. Kata kunci : tambang batu bara, kolam bekas tambang, kualitas air kolam.